2007
DOI: 10.1080/02841850701499409
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic venous variations in patients with congenital inferior vena cava anomalies: classification with computed tomography

Abstract: Eight types of pelvic venous variations of congenital IVC anomalies were classified using CT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
58
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 14 publications
5
58
0
1
Order By: Relevance
“…In this study, for a rare anatomic variation that was defined as type 2d, it was emphasized that the left lower extremity veins were continuing directly as left IVC to the left of the aorta, without uniting with the internal iliac vein (IIV), and the left IIV was being drained into the right IVC, uniting with the right main iliac vein. Our case also was partially similar to this rare anatomic variation defined by Morita et al, 4 but it differs from that variation in a few important ways. In our case, at the level of the left EIV beginning its course like the left IVC, a thick connection vein, which had an increment of calibration with the vein in question, was forming a connection with the right IVC to the slight upper of the left IIV connection level.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…In this study, for a rare anatomic variation that was defined as type 2d, it was emphasized that the left lower extremity veins were continuing directly as left IVC to the left of the aorta, without uniting with the internal iliac vein (IIV), and the left IIV was being drained into the right IVC, uniting with the right main iliac vein. Our case also was partially similar to this rare anatomic variation defined by Morita et al, 4 but it differs from that variation in a few important ways. In our case, at the level of the left EIV beginning its course like the left IVC, a thick connection vein, which had an increment of calibration with the vein in question, was forming a connection with the right IVC to the slight upper of the left IIV connection level.…”
Section: Discussionsupporting
confidence: 56%
“…If the dorsal portion of the circumaortic collar persists, the left renal vein is located posterior to the aorta, forming a retroaortic left renal vein. 4 Congenital anomalies of the IVC can be classified under the main headings of suprarenal segment, renal segment, and subrenal segment anomalies. Regarding double IVC, which is one of the important anomalies of the subrenal segment, there is a subject about persistence of the bilateral supracardinal veins.…”
Section: Discussionmentioning
confidence: 99%
“…The duplicated inferior vena cava has a reported incidence of 2-3% in autopsy studies [15,18]. However, this anomaly diagnosed by CT, was only 0.3-0.6% [13,16]. This difference in occurrence suggests that the smaller component is not readily apparent on CT.…”
Section: Duplication Of the Inferior Vena Cavamentioning
confidence: 59%
“…A radiological study by Morita et al [16] also found that such anomalies were significantly more common in men (39 of 3821 cases-1%) than in women (12 of 2473 cases-0.5%); men/women ratio is 2:1.…”
Section: Duplication Of the Inferior Vena Cavamentioning
confidence: 99%
See 1 more Smart Citation